Good for living? On the relation between globalization and life expectancy - Andreas Bergh; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2009)
This paper analyzes the relation between three dimensions of globalization (economic, social and political) and life expectancy using a panel of 92 countries over the period 1970-2005. Using different estimation techniques and sample groupings we find a very robust positive effect from economic globalization on life expectancy, even when controlling for income, nutritional intake, literacy, number of physicians and several other factors. The result also holds when the sample is restricted to low income countries only. For political and social globalization we find no robust effects.
Keywords: F02; H51; I10; 330; Globalization; health; life expectancy; development